Pattern of Knee Injury Cases Attending Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Knee injury one of the most common injuries among soldiers accounts for losses in efficient combat power as well as increase burden of disability placed to the different units of Armed Forces.Objectives: To find out the pattern of knee injury of patients attending at a tertiary military hospital.Materials and Methods: This descriptive cross-sectional study carried out during January 2017 to December 2017 at Orthopedic Center of CMH, Dhaka. A total of 153 knee injuries patients were selected purposively as per selection criteria and data were collected by face to face interview and record review.Results: Total 153 respondents’ mean age was 31.03±10.19 years, most of them (41.8%) were from age group 25-34 years and were male (90.8%). Anterior Cruciate Ligament (ACL) injury was predominant (37.9%) and main precipitating physical event was football (20.3%) followed by jumping 9 feet ditch (16.3%). Right knee was more involved (49.7%) than left knee (46.4%). Most of injuries occurred in the exercise ground (40.5%) then sports ground (35.3%). ACL injuries (19%) were common in the age group 25-34 years and 9.8% were in 15-24 years. Morbidity duration of knee injuries was